Analysis of Service Quality And Consumer Satisfaction Visitors Supermarket Superindo Airport City Mall Tangerang - Banten - Syamsu Alang (Magister Manajement Studies Program, 2020)
This study to conducted of determine the gap between the expected services and services perceived by visitors in the level of customer satisfaction with a service measured by comparing the expectations of consumers with the quality of service they want with the reality they receive or feel. Through the most appropriate factors between what is expected and what is felt by consumers of visitors, including the ease and completeness of the supply of various products, responsibility for quality and pricing, as well as responsibility for the safety of goods and the safety of visitors and buyers of Supermarket SuperindoBandara City Mall-Tangerang. The results describe attributes that are considered important by consumers in Quadrant A (the performance of the quality of services provided some have not been implemented properly), Quadrant B (the performance of quality of services provided has been carried out in accordance with consumer expectations), while attributes considered less important by consumers in Quadrant C (the performance of the quality of services provided is quite sufficient), Quadrant D, (the performance of the quality of the services provided is very good).